A national health service : draft memorandum on the government's proposals
1944-04-14 1944 1940s 14 pages DIAGRAM B The General Structure as relating to Hospital Services with particular reference to the formulation of the plan and its passage to the Minister as proposed by the British Hospitals Association. [diagram] Note The British Hospitals Association proposals provide that either the Joint Authority or the Local Hospitals Council or the Voluntary Hospitals may appeal direct to the Central Hospitals Board on any matters in dispute which are not satisfactorily determined in the Regional Hospitals Council. 292/847/2/33